Examining the Validity and Reliability of Antonovsky's Sense of Coherence Scale in a Population of Pregnant Australian Women. (June 2015) - Ferguson, Sally; Davis, Deborah; Browne, Jenny; Taylor, Jan
Antonovsky's Orientation to Life questionnaires were developed to measure sense of coherence (SOC). Although the SOC 13 instrument is widely used to measure health in general populations, it has not been assessed in pregnant women. If the SOC 13 is to be used to assess women's childbearing health, it requires further examination. The purpose of the research is to assess the psychometric properties of Antonovsky's SOC 13 questionnaire in pregnant women. When administered to 718 pregnant Australian women, the construct validity of the SOC 13 was difficult to establish. The SOC 9 was created by removing 4 items and provided best data fit. The SOC 13 and SOC 9 were found to have sound criterion validity, internal reliability, and equivalence between versions. It is hoped that the present study will stimulate additional research on SOC scales to examine their ability to assess women's childbearing health.